Efficient Protocol for Indirect Shoot Regeneration from Leaf Explants of Stevia rebaudiana (Bert.) – An Important Calorie Free Biosweetner - C.V.Naidu2, D. Preethi1, T.M.Sridhar1 and (Journal of Phytology, 2011)
Callusing response of various field grown and in vitro grown explants such as leaf was studied using various auxins (NAA/IAA/2,4–D) alone or in combination with cytokinins namely, BA/Kn. Either NAA/IAA in combination with BA or Kn induced profuse light green to dark green coloured, fragile to nodular callus formation from leaf explants. At higher concentration of auxins occasional root formation directly from the leaf explants was also observed. Indirect shoot organogenesis was achieved from the callus using BA (2.0 mg/L) where highest number of shoots (8.5 ± 0.1) with maximum frequency (86%) was regenerated. All the in vitro raised shoots with a length of 3-5 cm were transferred to rooting medium supplemented with different concentrations of auxins such as IBA and NAA (0.1–1.0 mg/L). The best rooting response was observed on 0.5mg/l IBA. The well rooted plantlets were transferred to polybags containing soil + vermiculite in 1: 1 ratio for hardening. Finally the hardened plantlets were transferred to field conditions for maximum survivability.